Effectiveness of Educational Intervention Based on Theory of Planned Behavior on Health Promoting Behaviors and Quality of Life among Infertile Women: Effectiveness of Educational Intervention Based on Theory of Planned Behavior on Health Promotion Behaviors and Quality of Life in infertile women - Foroughameri, Masoumeh; Hatami, Mohammad; Rafiepour, Amin; Nicknam, Mojgan (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:Infertility, as a cause of psychological stress, can lead to a crisis in patients. The present study aimed to investigate the effectiveness of the theory of planned behavior training on health-promoting behaviors and the quality of life of infertile women. Materials and Methods:This was a semi-experimental study with pretest, post-test, and follow-up designs and a control group. The statistical population included 30 infertile women selected by convenience sampling and were randomly assigned to the experimental and control groups. The experimental group underwent 6 sessions of 90 minutes of the theory of planned behavior training. Health Promoting Lifestyle Profile and WHOQOL-BREF quality of life were used to collect data. The data were analyzed by repeated-measures ANOVA using SPSS-22. Results:The results showed that the theory of planned behavior training significantly improves health-promoting behaviors (P<0.001) and quality of life (P<0.0001) in infertile women. Conclusion:It can be concluded that the theory of planned behavior training can improve health-promoting behaviors and quality of life in infertile women by changing their attitudes and cognition.